Effect of Service Quality on Integrated Antenatal Care Patient Satisfaction - Murti Dwi Handayani; Sentot Imam Suprapto; Nia Sari (Journal for Quality in Public Health, 2019)
The increase in the health service is very important to be made by health care provider institutions such as clinics in order to improve patient satisfaction. But in the last few years many decline the number of visits the patient at the clinic. This is due to the existence of the dissatisfaction felt by the patient over a given service. The purpose of the study to find out the influence of the quality of service to the satisfaction of the Patients current study. Design Integrated ANC namely observational analytic quantitative approach. The research of the variable quality of service as the independent variable and the dependent variable as patient satisfaction. The population of the research that is Integrated in the entire patient ANC Clinics Kupang (nutrition, BP, KIA, LAborat and Loket) Mojokerto with the average number of patients per month as many as 777 patients. Smapel taken with the technique of systematic sampling as much as 117 respondents. Data collected by questionnaire instrument and processed by using coding, editing, tabulating and scoring as well as tested with test statistic spearman rho and linear regression. Research results throughout the dimensions of service quality affects patient satisfaction whereas that can be seen from the value of ρ value < 0.05 for all dimensions so partial dimensions of service quality affects patient satisfaction. Similarly, on the results of the regression simultaneously or synchronously also showed the same results, namely the value of p value < 0.05, so can be conclusion that simultaneously or synchronously dimensions of service quality affects patient satisfaction